The phantom tracker; or, The prisoner of the hill cave - Dewey, Frederick H. (Salt Lake City, UT : Project Gutenberg, 2022)
"The Phantom Tracker; or, The Prisoner of the Hill Cave" by Frederick H. Dewey is a novel written in the late 19th century. The story appears to unfold across a rugged, desolate wilderness known as the Land of Silence, involving themes of adventure, treasure hunting, and conflict in the face of danger. Central to the narrative is Pedro Felipe, a Mexican scout, who embarks on a quest to find treasure hidden in a notorious cave after a thrilling rescue of his master's daughter from a band of robbers. At the start of the novel, the oppressive atmosphere of the scorching Gila River setting envelops the reader, showcasing nature's lethargy through the eyes of animal life observed in the heat. The narrative introduces Pedro Felipe, an experienced and cunning scout determined to seek a hidden treasure believed to be in a ghostly landscape, while his backstory reveals both admiration and ambition. As the opening chapters progress, another key character surfaces, Christina Wheeler, a spirited girl who becomes lost during an encounter with pursuing Apaches. The plot quickly escalates as a group of horsemen, along with Pedro, embark on perilous paths that intertwine their fates against the backdrop of a vast, unforgiving landscape, setting the stage for an exhilarating adventure rife with suspense and challenges. (This is an automatically generated summary.)
Release date is 2022-06-12
David Edwards, SF2001, and the Online Distributed Proofreading Team at https://www.pgdp.net (Northern Illinois University Digital Library)
Keywords: Ghost stories; Frontier and pioneer life -- Fiction; Outlaws -- Fiction; Apache Indians -- Fiction; Arizona -- Fiction; Abduction -- Fiction; Mexico -- Fiction; Dime novels; Comanche Indians -- Fiction; Wagon trains -- Fiction; Mexicans -- Fiction